Endocrine care of transpeople part I. A review of cross‐sex hormonal treatments, outcomes and adverse effects in transmen. (25th March 2015) - Meriggiola, Maria Cristina; Gava, Giulia
Summary Gender dysphoria (GD) is characterized by discomfort with the assigned or birth gender and the urge to live as a member of the desired sex. The goal of medical and surgical treatment is to improve the well‐being and quality of life of transpeople. The acquisition of phenotypic features of the desired gender requires the use of cross‐sex hormonal therapy (CHT). Adult transmen are treated with testosterone to induce virilization. In adolescents with severe and persistent GD, consideration can be given to arresting puberty at Tanner Stage II and if dysphoria persists, CHT is generally started after 16 years of age. Currently available short‐ and long‐term safety studies suggest that CHT is reasonably safe in transmen. Monitoring of transmen should be more frequent during the first year of cross‐sex hormone administration reducing to once or twice per year thereafter. Long‐term monitoring after sex reassignment surgery (SRS) includes annual check‐ups as are carried out for natal hypogonadal men. In elderly transmen, special attention should be paid to haematocrit in particular. Screening for breast and cervical cancer should be continued in transmen not undergoing SRS.